Renewable Energy in Nepal: Current State and Future Outlook - Raihan, Asif; Joarder, Sadman Anjum; Sarker, Tapan; Gosik, Blanka; Kusz, Dariusz; Zimon, Grzegorz (International Journal of Energy Economics and Policy, 2024)
Nepal’s energy mix is predominantly based on traditional and inefficient biomass and fossil fuels. As a result, there is a notable prevalence of energy scarcity in the country. Within the literature, there exists a lack of a comprehensive review of the potential of renewable energy in the country while the relatively less contribution of renewable energy resources, making the country more vulnerable to adopt a more carbon-intensive energy policy. Consequently, in this study, we conduct a thorough review of existing literature to provide a comprehensive assessment of the current status of renewable energy and the energy mix in Nepal. We also discussed the potential for the country to transition to a sustainable energy system. This review analysis exclusively focused on scholarly articles and research reports that specifically addressed the topic of renewable energy in Nepal. Despite the rapid decline in the cost of solar photovoltaics, Nepal’s renewable energy share currently stands at only 3.2%. This paper argues that Nepal needs proactive and favorable strategies and policies to effectively implement clean energy, based on the given premises and the country’s aspirations for sustainable energy. This involves a substantial amount of solar power production combined with battery storage, supplemented by storage methods such as off-river pumping hydropower technology. The study emphasizes the significance of renewable energy in achieving the United Nations’ Sustainable Development Goals (SDGs). This review also emphasizes the obstacles in the advancement of Nepal’s renewable energy industry and offers suitable policy suggestions to address these obstacles, hence facilitating a sustainable shift in energy.